Bioaccessible heavy metals-sediment particles from Reconquista River induce lung inflammation in mice - Ferraro, Sebastián Ariel (2012)
The Reconquista River (RR), one of the most polluted watercourses in Argentina, receives effluent discharges from heavily industrialized and highly populated settlements. During winter and summer, the floodplain remains dry, producing the oxidation of sulfide and organic matter present in the sediment, making heavy metals more bioaccessible. Dispersion of this sediment occurs, and thus harmful effects on the pulmonary health of residents and workers inhabiting the RR bank may take place. The authors characterized the sediment particles of the RR (RR-PM) morphologically by scanning electron microscopy and its elemental composition by energy dispersive X-ray spectroscopy (EDX) and Community Bureau of Reference (BCR) sequential extraction. Furthermore, the authors evaluated its biological impact on the respiratory system of BALB/c mice, generating four groups: control healthy, sensibilized with ovalbumin, exposed to particles, and sensibilized and exposed to particles. Sediment particles of the Reconquista River contained fine particulate matter, with a high concentration of bioaccessible Cu and Zn. The authors found that animal exposure to RR-PM caused polymorphonuclear cell lung infiltration, augmentation of O2-, increase of proinflammatory cytokines (tumor necrosis factor alpha [TNFα], interleukin-6 [IL-6]) and apoptosis. This adverse response was more dramatic in the sensibilized and exposed to particles group. Even more, they proved the bioaccessible fraction present in the RR-PM to be responsible for these harmful effects. The authors conclude that RR-PM produces an adverse biological impact on the airways of healthy animals, which is largely aggravated in previously sensibilized animals.